Kepuasan Pengguna dan Tantangan Pelayanan Angkutan Umum Perkotaan di Indonesia - Nurul Fitriani; Dani F. Brilianti; Reza Yoga Anindita; Pipit Rusmandani; Destria Rachmita (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2026)
The quality of public transport services in Tegal City from an operational perspective is still considered sub-optimal, as reflected in the low levels of comfort, punctuality, and a load factor of only around 13%. This study aims to analyze user characteristics, measure the level of satisfaction with public transport services, and formulate strategies for service improvement based on field data. A quantitative approach was employed through a survey of public transport users, using SERVQUAL analysis and the Customer Satisfaction Index (CSI). Assessment of 19 indicators shows that all service aspects are considered very important (average MIS 4.32), while satisfaction levels fall within the satisfied–fairly satisfied category (average MSS 3.65) with a CSI value of around 73%, indicating a remaining gap between expectations and reality. The main weaknesses lie in the availability of safety facilities (X4), waiting time (X6), service equality for vulnerable groups (X16), the roadworthiness of vehicles (X1), and driver attitude (X19). Therefore, service improvements need to focus on providing safety facilities and conducting regular inspections, reducing waiting times through more reliable scheduling and headways, developing inclusive services for the elderly, persons with disabilities, children, and pregnant women, undertaking fleet renewal and maintenance, as well as implementing training and enforcing a code of ethics to improve driver attitude and professionalism.